Fácies e petrografia da sucessão vulcanoclástica-siliciclástica pré-cambriana no testemunho AVL8-FD6, noroeste da Serra dos Carajás - COSTA, Franco Felipe Oliveira (2019)
In the southeast part of the Amazon Craton is located one of the biggest metallogenic provinces in the world, Carajás Mineral Province, which is an expressive geomorphological setting, comprising E-W oriented mountains and plateaus. It contains a large precambrian sedimentary register, covered, however, by a dense forest and soils. The most appropriate procedure to obtain complete stratigraphic data in an area with these difficulties is, no doubt, the description and interpretation of drill hole samples, in which this research is concerned. The drill hole AVL8-FD6 (Salvador Target) samples were collected in the northeast part of Carajás Mountain, near Igarapé Bahia Mine, southeast of Pará State, and were given by Vale mining company. It corresponds to a vulcanoclastic/siliciclastic sequence, represented by vulcanoclastic deposits associated with rare siliciclastic levels; in erosive discordant contact (S1) meanly with siliciclastic rocks associated with vulcanoclastic secondarily; subdivided in the lithostratigraphic units Igarapé Bahia Group and Águas Claras Formation. Both cut by mafic nature gabroic bodies. The petrographic study of this succession allowed the distinction of six lithofacies: chlorotized quartz-sandstone (Am), tuff crystal ignimbrite (Ict), foliated ignimbrite (If), lapilli ignimbrite (Itl), quartz-sandstone with cross lamination (Acz) and quartz-sandstone with almost planar-lamination (Aq). The hydrothermalism was responsible for the large modifications in the lithofacies, sometimes obliterating the primary structures, mainly in the ignimbrites and tuffs, leading to the chlorite autigenesis and pumice devitrification. The succession is all affected by hydrothermal alteration, accompanying chlorotizarion, carbonatization and sericitization. The integrated review suggests that the drill hole AVL-FD6 basal lithofacies, attributed to Igarapé Bahia Group were deposited in a subaerial volcanic basin; and the lithofacies related to Águas Claras Formation were deposited in continental a basin, in a fluvial environment, disturbed by magmatic events in its initial phase.